The Impact Of Agricultural Loans by Deposit Money Banks on Agricultural Output In Nigeria - Magaji, Sule; Yisa, Samuel; Peter O, Achi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study examines the impact of agricultural loan by deposit money bank credit on agricultural output in FCT Abuja, Nigeria. The study employed the Demand-following theory to explain the relationship between agricultural loan applicant access to deposit money bank credit and agricultural output. A sample of 295 (5 Agricultural loan desk officer from the five selected banks and 200 agricultural loan applicants) respondents were sampled using Multistage Cluster sampling technique. Data were analysed using descriptive statistic (mean Score) and logit regression analysis for inferential statistics. The results show that agricultural loan applicants' access to bank credit for deposits has a large direct impact on Nigerian agriculture. Based on the outcome of data analysis, the study recommends that the Apex bank should direct the deposit money banks to make credits available for agricultural loan applicants and upsurge the agricultural credits monetary base to farmers. This can be done by expanding and encouraging more farmers and also increasing the sum allotted to individual/cooperative units.